Civil society organizations and their role in achieving sustainable development - Saba Hamid Hussein; Sun Abbas Jassim (Zanco Journal of Humanity Sciences)
The subject of this study revolves around the role of civil society in protecting the environment and achieving sustainable development that has preoccupied many scholars and writers, as this topic has not received its right to adequate attention and research.